A New Epistemic Silk Road? The Chinese Knowledge Diaspora, and its Implications for the Europe of Knowledge. (2nd April 2015) - Welch, Anthony
Abstract : The paper examines the implications of the extensive and increasingly significant Chinese knowledge diaspora for the Europe of Knowledge. Based on extensive fieldwork, the paper examines the size, significance and key issues surrounding the growth of the Chinese Knowledge Diaspora. A portrait is developed of a highly-skilled group (bi-lingual and bi-cultural) who have the capacity to contribute to teaching and research both in China and their host nations, and who are often willing and eager to act as a bridge between both sides. Reference is also made to China's numerous Overseas Talent Recruitment Schemes, which often target such individuals, and to the significance of this group to China's dramatic, and ongoing, scientific rise. Key issues are discussed, as well as some limitations and the prospects for the future. Based on available information, data on PRC students and academics in Europe are presented and an assessment made of both the potential, and of the relatively limited impact, compared with major English-language countries of migration, such as the US, Canada and Australia. The analysis concludes with an assessment of prospects for a new epistemic Silk Road, and some of the barriers to its development.